2019
DOI: 10.1007/s00125-019-05029-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-functional changes in eNAMPT at high concentrations mediate mouse and human beta cell dysfunction in type 2 diabetes

Abstract: Aims/hypothesis Progressive decline in functional beta cell mass is central to the development of type 2 diabetes. Elevated serum levels of extracellular nicotinamide phosphoribosyltransferase (eNAMPT) are associated with beta cell failure in type 2 diabetes and eNAMPT immuno-neutralisation improves glucose tolerance in mouse models of diabetes. Despite this, the effects of eNAMPT on functional beta cell mass are poorly elucidated, with some studies having separately reported beta cell-protective effects of eN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 44 publications
(64 reference statements)
0
39
1
Order By: Relevance
“…All this data suggests that eNAMPT selectively antagonizes Rantes-dependent calcium signaling. Very recently, Sayers et al, demonstrated a modulation of calcium release mediated by eNAMPT, which, as a dimer, increased glucose-stimulated intracellular calcium levels [23]. In this respect, in our model we were unable to appreciate any effect of eNAMPT alone at the concentrations tested (500-1000 ng/mL = 9-18 nM).…”
Section: Enampt Antagonizes Ccr5 Activation In Hela-ccr5 Cellscontrasting
confidence: 54%
See 1 more Smart Citation
“…All this data suggests that eNAMPT selectively antagonizes Rantes-dependent calcium signaling. Very recently, Sayers et al, demonstrated a modulation of calcium release mediated by eNAMPT, which, as a dimer, increased glucose-stimulated intracellular calcium levels [23]. In this respect, in our model we were unable to appreciate any effect of eNAMPT alone at the concentrations tested (500-1000 ng/mL = 9-18 nM).…”
Section: Enampt Antagonizes Ccr5 Activation In Hela-ccr5 Cellscontrasting
confidence: 54%
“…To add to the complexity, it has been recently demonstrated that the effects on pancreatic beta cell functional mass of eNAMPT are bimodal and concentration and structure functionally dependent [23]. In our study, we used concentrations between 250 and 1000 ng/mL (corresponding to 4.5-18 nM), with the only exception of internalization and cell labelling experiments, in which higher concentrations were used to counteract the higher concentrations used of RANTES (in the second instance, RANTES induces rapid internalization only at high concentrations, while in the first instance RANTES-PE binding could be appreciated only at higher concentrations).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work by Revollo and colleagues using Nampt-deficient mice [45] established the importance of NAD + in the regulation of β -cell insulin secretion. Subsequent studies have demonstrated the protective effects of NAD + modulation in isolated islets, through pre-incubation with NAD + precursors and enzymes, before functional assessments such as apoptosis and GSIS measures [46,47]. Here, oral NMN administration in obese mice did not induce any benefits on islet insulin secretion capacity.…”
Section: Discussionmentioning
confidence: 81%
“…The role of eNAMPT has been indicated to be inflammatory promotion, inflammatory suppression (Revollo et al, 2007;Li et al, 2008;Pillai et al, 2013;Zhao et al, 2013;Jing et al, 2014), enhancement of food intake (Brunetti et al, 2012), and regulation of insulin resistance as well as plasma free fatty acid concentration (Stromsdorfer et al, 2016;Nielsen et al, 2018). The function of eNAMPT remains elusive in recent research, demonstrating that low concentration of dimeric eNAMPT benefited for beta cell function through NAD+, however, a higher monomeric eNAMPT level presented hostile effect on beta cell function (Sayers et al, 2020). Obesity has also been associated with the dampened NAD+/SIRT pathway in adipose tissue (Jukarainen et al, 2016).…”
Section: Obesitymentioning
confidence: 99%